The Characteristics of Patient Disorders Treated in the Acute Room - PH, Livana; Anggraeni, Rina; Indrayati, Novi; Kurian, Midhu; Ar Ruhimat, Imroati Istibsyaroh; Suerni, Titik; Kandar, Kandar; Sujarwo, Sujarwo; Maya, Anita; Nugroho, Arief (Jurnal Ners Widya Husada, 2020)
Mental disorder patients who are treated in acute rooms averagely stay for 4 days. This will result in frequent changes of patients, so that old patients will meet new patients who have various nursing problems such as the risk of violent behavior, hallucinations, and delusions. The study aimed to determine the characteristics of mental disorder patients treated in the acute room. Quantitative research with a descriptive approach was carried out on 30 patients in the acute room of regional psychiatric hospital Dr. Amino Gondohutomo, Central Java Province. Data collection tool was questionnaire. The sampling technique used was Purposive Sampling Technique. Research data were analyzed univariately using frequency distribution. The results showed that the majority of respondents aged 26-35 years, the last education of respondents was basic education (elementary, junior high school/equivalent), and working in private sector, respondentsâ€™ caregivers were parents (father/mother) and children, and were treated for a majority of 7 days.Â Keywords: characteristics, mental disorder patients, acute roomÂ